The Capitalization of the Cultural Value of the Mabbarasanji Tradition from a Cultural Economics Perspective: An Analysis of the Treatment of Cultural Assets Based on Local Wisdom - Nuranjani Nuranjani; Gading Rayhan Al-ikbar; Muhammad Yamin; Roy Sakti Prasetya (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the Mabbarasanji tradition within the Culili neighborhood, Polewali Urban Village, Bone Regency, evaluating its structural dynamics as a non-monetary cultural asset from a cultural economics perspective. Utilizing an interpretive qualitative research design and phenomenological analysis, the inquiry captures the lived experiences of traditional reciters and local activists to understand how this oral performance generates localized social capital and maintains communal continuity. The findings indicate that the tradition represents a vital heritage resource whose value is determined by poetic auditory cadences, linguistic preservation, and collective voluntary labor. The investigation demonstrates that these customary practices directly satisfy the legal criteria established under Indonesian Law Number 5 of 2017 concerning the Advancement of Culture, thereby qualifying for formal institutional protection. To counteract modern threats of globalization and declining youth participation, this study devises a narrative Cultural Accounting Disclosure Framework that operationalizes qualitative sustainability metrics for state registries. Ultimately, this framework bridges the gap between abstract local wisdom and formal accountability systems, ensuring the sustainable preservation of Bugis cultural identity.